2003
DOI: 10.1029/2002jc001325
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among tracer ages

Abstract: [1] Measurements of chemical tracers whose spatial gradients are primarily due to the time dependence of sources and/or sinks are often used to define ''tracer ages'' in an effort to diagnose transport. However, a major problem with interpreting these tracer ages is that different tracers can yield different ages, and at present, it is not clear what aspects of the transport are measured by the different tracers. We use the concept of a distribution of transit times to compare the timescales derived from diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
306
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(324 citation statements)
references
References 42 publications
(78 reference statements)
17
306
1
Order By: Relevance
“…[14] Waugh et al [2003] evaluated the ability of several tracer pairs to constrain D/G, illustrated in their Figure 8. It is evident from their Figure 8 that CFC-12 and a radioactive tracer with a decay rate similar to the atmospheric CO 2 growth rate is one of the more suitable pairs.…”
Section: Determination Of Ttd Parametersmentioning
confidence: 99%
“…[14] Waugh et al [2003] evaluated the ability of several tracer pairs to constrain D/G, illustrated in their Figure 8. It is evident from their Figure 8 that CFC-12 and a radioactive tracer with a decay rate similar to the atmospheric CO 2 growth rate is one of the more suitable pairs.…”
Section: Determination Of Ttd Parametersmentioning
confidence: 99%
“…These differences can be understood through the conceptual framework of Transit Time Distributions (TTDs) (also called "age spectra" and "transit time probability density functions" [10,26]). The TTD is a probability distribution of age, which explicitly accounts for the fact that a water mass is comprised of a mixture of components with different ages, each with different advective and diffusive histories.…”
Section: Introductionmentioning
confidence: 99%
“…Doney et al, 1997;Fine et al, 2002), but the estimated tracer ages often vary with different tracers. Recent studies on tracer transport have pointed out that in the ocean, where advective-diffusive mixing is prevalent, water masses in the ocean interior have a continuous distribution of transit times since its last contact with a surface, rather than a single transit time (Haine and Hall, 2002;Holzer and Hall, 2000;Waugh et al, 2003). They have shown that tracer ages are differently weighted averages over the transit times that vary from tracer to tracer (Holzer and Hall, 2000;Khatiwala et al, 2001; Wunsch and Heimbach, 2008), and do not represent the age distribution of the water mass.…”
Section: Apparent Transit Time Of Pbmentioning
confidence: 99%